ANALISIS PENGARUH OPINI GOING CONCERN,LIKUIDITAS,SOLVABILITAS,ARUS KAS, UMUR PERUSAHAAN DAN UKURAN PERUSAHAAN TERHADAP KEMUNGKINAN FINANCIAL DISTRESS - Puji Astuti; Sugeng Pamudji (Diponegoro Journal of Accounting, 2015)
This study analyzes the impact of going concern opinion, financial actor’s like liquidity, solvability, cash flow, and non financial factor’s like size of firm and age of firm on probability of financial distress.. Population that use in study is 468 listed manufacturing firms in Indonesia Stock Exchange in 2010 -2013. This study analyzes with purposive sampling method. A criterion for firm with probability of financial distress is a company which is has interest coverage ratio less than 1 .By omitting companies with some data unavailable, the samples consist of 348 companies firmsLogistic regression used to be analysis technique.The result show that going concern opinion have positive significant afeect to financial distress, liquidity and cash flow have negative significant affect to financial distress, age of firm, solvability, and size of firm not affect to financial distress